DETERMINING THE EMPATHIC SKILL LEVELS OF CHILDREN BY THEIR DOMESTIC FACTORS - Meral TANER DERMAN (Fırat University, 2019)
The aim of this research is to determine the empathic skill levels of 10-11 year old children by their genders and domestic factors. The data have been collected through 3199 children, 1587 of whom are girls and 1612 of whom are boys, going to 10 schools from different socioecnonomical levels in Bursa. Empathy Scale for Children, which was developed by Byrant (1982) and adapted to Turkish by Yılmaz-Yüksel (2003) and the Information Form that has been prepared by the researchers have been used as the data gathering tools to measure the empathy skills of children. Correlation Analysis, One-way Analysis of Variance (ANOVA) and t-Test have been used for analysing and interpreting the acquired data. And Tukey's HSD Test has been used in order to find the source of the difference. Significance levels of 0,01 and 0,05 have been sought during the analysis and interpretation processes. It has been determined that girls have more emphatic skills than boys; emphatic skill levels of children don't differ by the socioeconomic levels and marital statuses of their families; they don’t have any relation with the ages of parents, children number of the family and the rank of the child; and children from families formed of only parents and children, have higher empathic skill levels than other children. Also, it has been determined empathy skill levels of children described as naughty were less likely than other children; children from family which observed aggressive behavior have less empathic skill levels than other children.